Diversity of endophytic fungi in rubber roots and their antagonistic activity against Rigidoporus lignosus (Klotzsch) Imezaki / Mohd Akhbar Muqriz Abdul Wahed - Abdul Wahed, Mohd Akhbar Muqriz (Faculty of Plantation and Agrotechnology, 2015)
Rubber is one of the 1110st important commodities in our country. The incidence of pest and disease can negatively the affect the yield of this crop. One of the worst diseases is white root disease caused by Rigidoporus lignosus . This research was conducted to identify the presence and diversity of endophytic fungus in the roots of this crop and to examine the potential of biological control agents through these endophytes. The result of this study shown there is difference between commercial rubber and wild rubber in the aspect of diversity where commercial rubber has high percentage of endohytic fungus which is eighty-one percent from the total of eighty-nine isolates. Next, there are certain endophytes that managed to control the pathogen growth up to fifty percent namely F3 and F4.